Association between maternal and fetal outcomes in high BMI diabetic and non-diabetic groups - Kabir, Rezwana; Parvin, Sumona; Islam, M. Ubaidul; Begum, Ferdousi (International Journal of Contemporary Pediatrics, 2020)
Background: BMI has increased among the women of reproductive age worldwide. Insulin resistance associated with obesity and diabetes are mostly responsible for the adverse outcomes like macrosomia, maternal morbidity, increased operative interference and NICU admission. Objectives of the study was to assess maternal high BMI and its association with maternal and neonatal outcomes in diabetic and non-diabetic groups. Methods: A cross sectional study was conducted in the BIRDEM General Hospital Dhaka on 200 pregnant women with high BMI at 3rd trimester. Patients were allocated in two equal groups- Group I Diabetic and group II Non-diabetic. Results: Age range was 18 to 35 years with mean age of 26.9±8.3 years among diabetic and 25.7±7.8 years among non-diabetic women. BMI was comparatively higher in diabetic group. Overall frequency of C/S was higher (89.5%) and on comparison between the groups, frequency was significantly higher in diabetic group (94% vs 85% in group I and group II respectively). The postpartum complications were also significantly higher in diabetic group (22% vs 7% in Group I and Group II respectively). About 23 (11.5%) of the babies had birth weight more than 3.5 kg (maximum among diabetic mothers 15% vs 8% in group I and II). The mean birth weight was higher in diabetic group 3.7 ± 0.4 kg vs 2.6±0.5 kg in non-diabetic group respectively. On the neonatal outcomes, significant number of macrosomia were found in the diabetic group, and NICU admissions were also higher in the diabetic group. Conclusions: High BMI diabetic mothers have significantly higher maternal and neonatal complications.